Reassessing the position of Isinay in the Central Cordilleran Family - Reid, Lawrence A. (2019)
Access online through this link: https://journals.upd.edu.ph/index.php/archive/issue/view/689
Keywords: Isinay language; Cordillera Administrative Region; Phonology